Relational risk management in a Psychologically Informed Planned Environment (PIPE) approved premises. (September 2019) - Chapman-Gibbs, Petra; Mannix, Karyn; Harvey, David
Psychologically Informed Planned Environments (PIPEs) have been developed as part of the Offender Personality Disorder Strategy (Department of Health, 2011 ). The Yorkshire and Humberside Personality Disorder Partnership (YHPDP) supports the delivery of this strategy at a local level, which includes two PIPE Approved Premises (AP). We have found that one of the most challenging and important aspects of running a PIPE AP has been responding to rule-breaking in a psychologically-informed manner. This paper describes a stepped and structured framework which we developed for managing boundary violations that is in line with the PIPE ethos.